Pengaruh Digitalisasi terhadap Kinerja UMKM (Studi pada KUKM di Provinsi Banten) - Ramdansyah, Agus David; Ganika, Gerry (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2024)
The development of technology has an impact on increasing competition in business. MSMEs also experience this in Banten, which forces them to rethink their business models. To survive and compete, many businesses have focused on the application and use of digital technology. Several studies have shown that digital technology can facilitate business continuity and increase their resilience to shocks This study aims to analyze the level of digitalization of MSMEs in regencies and cities in Banten Province and the obstacles they face in digitizing their businesses. In addition, to examine the extent to which the use of various forms of digital technology can stimulate the growth of MSME performance. This analysis covers 4 regencies and 4 cities in Banten Province, namely: Serang Regency, Pandeglang Regency, Lebak Regency, Tangerang Regency, Tangerang City, Cilegon City, Serang City and South Tangerang City. This study is based on data available at the Ministry of Cooperatives and MSMEs, BPS, and survey results. The results of this study aim to complement the literature that focuses on the digitalization of MSMEs, especially highlighting the gap between regencies and cities in Banten Province in terms of digitalization. In addition, this study also aims to determine the impact of digital technology on the performance of MSMEs in regencies and cities in Banten Province. The results of this study indicate the importance of MSME digitalization so that companies can become drivers of economic growth. This research topic is also expected to attract researchers who care about business digitalization and decision-makers at various levels who can help identify the right steps to stimulate digital innovation and investment in information and communication technology infrastructure.